PELESTARIAN KOLEKSI SASTRA SUNDA DI PERPUSTAKAAN AJIP ROSIDI - Dinda Puspita Dewi; Rifqi Zaeni Achmad Syam; Rosiana Nurwa Indah (Nusantara Journal of Information and Library Studies (N-JILS), 2020)
This study is to determine the implementation of preservation activities in the Ajip Rosidi Library in terms of how to save the value of information, how to save the physical form of Sundanese literature collections that are owned, and the obstacles faced in implementing the preservation of Sundanese literature collections. The method used in this research is descriptive research method. with a qualitative approach. Data collection techniques by means of observation, interviews and documentation study. There are two informants in this study. The results show that in order to save the value of the collection information, the library has converted the 200-year-old Sundanese Literature collection into microfilm or microfish which later, due to technological developments, was converted into CDs and hard drives. In saving the physical form of the collection, librarians carry out activities of mending, binding, giving silica gell, cleaning manually, and making policies in the form of library regulations. As for the obstacles experienced during the implementation of preservation of Sundanese Literature collection, namely related to human resource factors, funding factors, and environmental factors.Keywords: preservation; sundanese literature collection; ajip rosidi libraryABSTRAKPenelitian ini untuk mengetahui pelaksanaan kegiatan pelestarian di Perpustakaan Ajip Rosidi dilihat dari cara menyelamatkan nilai informasi, cara menyelamatkan bentuk fisik koleksi sastra sunda yang dimiliki, dan hambatan yang dihadapi dalam melaksanakan pelestarian koleksi sastra sunda.. Metode yang digunakan dalam penelitian ini adalah metode penelitian deskriptif dengan pendekatan kualitatif. Teknik pengumpulan data dengan cara observasi, wawancara serta studi dokumentasi. Informan dalam penelitian ini berjumlah dua orang. Hasil penelitian menunjukkan bahwa dalam menyelamatkan nilai informasi koleksi, maka perpustakaan mengalih bentukkan koleksi Sastra Sunda yang memiliki umur 200 tahun kedalam bentuk microfilm atau microfish yang kemudian karena perkembangan teknologi diubah dalam bentuk CD dan hardisk. Dalam menyelamatkan bentu fisik koleksi, maka pustakawan melakukan kegiatan mending, penjilidan, pemberian silica gell, membersihkan secara manual, dan membuat kebijakkan berupa peraturan perpustakaan. Adapun hambatan yang dialami pada saat pelaksanaan pelestarian koleksi Sastra Sunda, yaitu berkaitan dengan faktor sumber daya manusia, faktor pendanaan, dan faktor lingkungan.